Identification and Regioselectivity of a 4'‐O‐Methyltransferase From Chemically Diverse Populations of Chrysanthemum - Dan Yang; Yuetong Yu; Lixin Yang; Chen Kang; Zhimin Wang; Sha Chen; Jingjing Zhu (Food Frontiers)
ABSTRACT Chrysanthemum morifolium Ramat, as food and drug homolog material, exhibits unique pharmacological activity due to richness in diverse flavonoids. Chrysanthemum cultivated in northern China is particularly rich in 4'‐methoxylated flavones, yet the mechanism responsible for methoxyflavone biosynthesis in chrysanthemum remains elusive. In this study, an O‐methyltransferase (OMT) (CmOMT3) from chrysanthemum was isolated and identified as a class II OMT through phylogenetic and sequence analysis. To evaluate the biotechnological potential of CmOMT3, 12 flavonoids and phenolic acids were biotransformed using CmOMT3‐transformed Escherichia coli, revealing that recombinant CmOMT3 transfers methyl to the hydroxyl group at C‐4' position of multiple phenylpropanoid compounds with broad substrate selectivity. The catalytic conversion rates of CmOMT3 were notably high for eriodictyol (77.4%) and chlorogenic acid (53.34%), followed by luteolin (49.42%) and caffeic acid (37.77%). Through molecular docking and site‐directed mutagenesis, key residues Asn123 and His175 of CmOMT3 had lowest binding energy when mutated to His (−4.76 kcal/mol) and Met (−5.96 kcal/mol), respectively. The mutants N123H and N123A enhanced catalytic activity with substrate conversion of apigenin (1) increased from 8.49% for wild‐type CmOMT3 to 46.70% and 30.46%, respectively. This study represents the first report of an OMT exhibiting broad substrate specificity, catalyzing the 4'‐O‐methylation of flavonoids in chrysanthemum. It sheds light on the molecular basis for the high methoxyflavonoids’ levels in northern chrysanthemums and lays the groundwork for molecular breeding aimed at enhancing methoxyflavonoid production in chrysanthemum cultivars.